An evaluation of intradermal all-in-one vaccine based on an inactivated recombinant Mycoplasma hyopneumoniae strain expressing porcine circovirus type 2 (PCV2) capsid protein against Korean stains of PCV2d and M. hyopneumoniae challenge. (November 2022) - Suh, Jeongmin; Oh, Taehwan; Chae, Chanhee
Abstract: This study evaluates the efficacy of intradermal all-in-one vaccine (MHYOSPHERE® PCV ID, Laboratorios Hipra S.A. Amer, Spain) based on the strain Nexhyon, an inactivated recombinant M. hyopneumoniae strain with an embedded/integrated PCV2a capsid protein thereof, as the single active substance. Pigs were administered the vaccine intradermally at 21 days of age with 0.2 mL, then challenged at 49 days of age with either M. hyopneumoniae (intratracheal route), PCV2d (intranasal route), or both. Upon dual challenge, growth performance was improved when the intradermal all in one vaccine was administered compared to the unvaccinated group. In pigs receiving single or dual challenge, vaccination increased neutralizing antibodies against PCV2d and specific interferon-γ secreting cells for each pathogen. In contrast, viral load of PCV2d in the blood, M. hyopneumoniae load in the larynx, and the severity of pulmonary and lymphoid lesions were decreased. Vaccination provided good protection against challenge with M. hyopneumoniae and PCV2d.